Ice-rock avalanche of 2002 in Genaldon River valley, North Caucasus, Russia: consequences and problems - Zaporozhchenko, E. V. (Journal of Nepal Geological Society, 2006)
The biggest glacial disaster in the Russian history occurred in September 2002. A huge ice- rock-water flow from the Kolka Glacier went down the Genaldon River valley with a speed of 320 km/h. Having travelled a distance of 18.5 km, it was stopped by the 2 km long narrows of the Rocky Mountain Range and it filled the hollow with 120 ml of deposits. The ice rock-water mass pressed through the narrows forming a debris flow which went down the valley for 10 km devastating all the settlements on the riverbed. As a result, 125 people lost their lives. In 2002, two months before the disaster, a series of collapses from an elevation of about 1000 m at the backside of the glacier had activated the avalanche. The last ice- mass collapse had a volume of 10 million ml. The material accumulated in the glacier hollow was knocked off and went down the valley. The 100-150 m high ice- rock- water mass (with air also) was moving down the 400- 500 m wide valley. The flow on its way down the valley trough was fed by the frontal masses of three huge ancient landslides situated on the left bank. The hazards and risks after 2002 can be attributed mainly to the filling up of the hollow by the ice-rock material, the formation of a dammed lake, and the filling up of the narrows by debris flow and mudflow deposits. Presently the dammed lake is discharging naturally and there is about 0.5 million ml of water in it. The future behaviour of the ice-rock dam is not clear and it is difficult to make any forecast due to its melting on the one hand and the formation of underground outflows with sporadic floods on the other hand. In 2002-2004 the debris flow deposits on the riverbed were still unstable and loose. A surge with a discharge of more than 20 m3/sec and (or) a storm flood of such a magnitude can adversely affect the riverbed processes in the overpopulated foothill areas requiring mitigation and protective measures.